Pathogenicity, transmissibility, and receptor binding of a human-isolated influenza A (H10N5) virus - Mengchan Hao; Jiaying Wu; Lina Ji; Yubo Zhao; Shunyuan Zhang; Yiwei Guan; Liangyu Li; Wenxue Yang; Yuan Zhang; Jianjun Chen (mBio)
ABSTRACT Recently, human infections with H10 influenza viruses, including H10N8 and H10N3, have been reported. In January 2024, a case of H10N5 and H3N2 co-infection was reported in Zhejiang Province, China, which is the first human infection with H10N5 avian influenza virus (AIV) globally. Almost simultaneously, we isolated a wild bird-derived H10N5 strain similar to the human H10N5 strain. To assess the public health risk, it is necessary to understand the zoonotic characteristics of these novel H10N5 viruses. Here, we evaluated the biological characteristics of human H10N5, wild bird H10N5, as well as poultry H10N8 in vitro and in vivo. We demonstrate that the novel H10N5 isolates infected and replicated effectively in human lung epithelial cells. They infected BALB/c mice without adaptation, which exhibited robust pathogenicity and caused mouse death. In guinea pig transmission experiments, the H10N5 strain spread through neither direct contact nor airborne exposure, whereas H10N8 transmitted effectively. Additionally, H10N5 exhibited dual receptor-binding characteristics with a stronger preference for avian receptors. The current public health risk of H10N5 is low. However, the occasional spillover infections of H10 AIV into humans and dual receptor-binding characteristics suggest a potential risk of cross-species transmission.IMPORTANCEIn 2024, the H10N5 AIV was first reported to infect humans. Concurrently, we isolated a strain of H10N5 from wild birds that was highly similar to the human H10N5 strain. However, the zoonotic potential and the associated public health risks of the H10N5 virus remain unclear. In this study, we systematically evaluated the replication characteristics of human H10N5, wild bird H10N5, and poultry H10N8 in human lung epithelial cells, the virulence in mice, the transmission capabilities in guinea pigs, and the receptor-binding properties. Our results demonstrate that these novel H10N5 viruses have not yet acquired the ability to transmit in guinea pigs, but they possess the potential to infect mammals. These findings provide timely insights and warnings for the development of public health prevention strategies.